2023
DOI: 10.1039/d2ta08921a
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed titanium-based metal–organic frameworks for visible-light activated chemiresistive sensing

Abstract: Simultaneously realizing high sensitivity and high selectivity at room temperature is still big challenge for designing chemiresistive gas sensing materials. In this work, the first visible-light active MOF sensing material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…IR spectra of I 2 @ 1 and I 2 @ 2 show that there are slight redshift and broadening of the peaks at 1400–1600 nm (characteristic peaks of N–C, NC), suggesting that the electronic environment in the vicinity of the N–C/NC bonds has changed (Figures S5 and S6). These results indicate that the triazine and imine groups as active sites interact with I 2 . , In addition, Raman spectroscopy further showed that there are new peaks near 110 and 160 cm –1 for I 2 @ 1 and I 2 @ 2 that appear compared with the as-synthesized one (Figure c,d). According to similar literature, the peak of 160 cm –1 can be attributed to I 2 or I 5 – within the pores, and the peak at 110 cm –1 indicates the presence of I 3 – bound to the internal surface of the framework .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra of I 2 @ 1 and I 2 @ 2 show that there are slight redshift and broadening of the peaks at 1400–1600 nm (characteristic peaks of N–C, NC), suggesting that the electronic environment in the vicinity of the N–C/NC bonds has changed (Figures S5 and S6). These results indicate that the triazine and imine groups as active sites interact with I 2 . , In addition, Raman spectroscopy further showed that there are new peaks near 110 and 160 cm –1 for I 2 @ 1 and I 2 @ 2 that appear compared with the as-synthesized one (Figure c,d). According to similar literature, the peak of 160 cm –1 can be attributed to I 2 or I 5 – within the pores, and the peak at 110 cm –1 indicates the presence of I 3 – bound to the internal surface of the framework .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the triazine and imine groups as active sites interact with I 2 . 40,41 In addition, Raman spectroscopy further showed that there are new peaks near 110 and 160 cm −1 for I 2 @1 and I 2 @2 that appear compared with the as-synthesized one (Figure 2c,2d). According to similar literature, the peak of 160 cm −1 can be attributed to I 2 or I 5 − within the pores, and the peak at 110 cm −1 indicates the presence of I 3 − bound to the internal surface of the framework.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Titanium-based metal–organic frameworks (Ti-MOFs) are one of the most active research fields of MOFs due to their intriguing catalytic properties. Contrary to their extensive performance research, the number of reported Ti-MOFs is extremely limited even after more than 20 years of continuous efforts. According to the hard and soft acid and base (HSAB) theory, the widely used carboxylate-based ligands can be regarded as hard bases, which will fast react with hard acid Ti 4+ ions, making the syntheses of titanium carboxylate-based MOFs extremely challenging. , To overcome this problem, the modulator method by employing low nuclear titanium-oxo clusters (TOCs) or coordination compounds as precursors and monocarboxylic acid as modulators has been developed. , The in situ decomposition of TOCs can slowly release Ti 4+ ions, and a large amount of monocarboxylic acid may suppress the deprotonation of organic linkers and competitively coordinate with the metal center, which helps in the formation of Ti-MOFs .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are porous materials that consist of metal ions or clusters linked by organic ligands and have a large surface area and tunable properties, which make them attractive as photocatalysts for hydrogen production. One of the main advantages of MOF materials over the aforementioned photocatalysts is their structural designability. This diversity means that building blocks and target structures should be chosen to better exploit the MOFs as photocatalysts. At the same time, the well-defined crystal structure of MOFs can be used not only to clarify the structure–function relationship but also to facilitate charge transfer. As heterogeneous catalysts, MOFs are readily separated from the reaction mixture and used for recycling.…”
Section: Introductionmentioning
confidence: 99%